PENERAPAN SANKSI HUKUMAN DISIPLIN TERHADAP NARAPIDANA YANG MELAKUKAN TINDAKAN KEKERASAN DI RUMAH TAHANAN NEGARA KELAS IIB PADANG - Eggy Rinanda Putra, FITRA OKTORINY dan (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Sanctions are the power to force someone to obey certain social rules and regarding legal sanctions to fulfill an agreement or comply with the provisions of the law. According to Article 1 paragraph (7) of the Minister of Law and Human Rights Regulation Number 6 of 2013 concerning the rules of correctional institutions and state detention centers, what is meant by disciplinary punishment is the punishment imposed on prisoners or detainees as a result of committing acts that violate prison rules and regulations. or prison. The problems that the author raises in this thesis are the application of disciplinary sanctions against convicts who commit acts of violence in the class IIB Padang state detention center, obstacles to the application of disciplinary sanctions against prisoners who commit violent acts in the class IIB Padang state detention center and efforts to overcome obstacles to implementation. Disciplinary Punishment Sanctions Against Prisoners Who Commit Acts of Violence in the Class IIB Padang State Detention Center. The author conducted research using a sociological juridical approach, while the nature of the research is descriptive. Data collection techniques through interviews and literature study, then processed through editing, coding and tabulating processes and analyzed qualitatively. Based on the research results, it can be concluded that: The application of disciplinary sanctions against convicts who commit acts of violence in the Class IIB Padang Detention Center means that each inmate is subject to disciplinary sanctions which have been regulated in the Minister of Law and Human Rights Regulation Number 6 of 2013 concerning Correctional Institution Rules and the State Detention Center. The sanctions given are in the form of confinement for 2 or 3 days in a detention cell such as a cell trap in the form of a prison within a prison because in this room the prisoner's movements are restricted from socializing with fellow prisoners. Obstacles to the Implementation of Disciplinary Sanctions against Prisoners Who Commit Violent Acts in the Class IIB Detention Center in Padang, the number of personnel is still small when compared to the number of inmates (inmates) in the Class IIB Detention Center in Padang. Class IIB Detention Center in Padang There must be additional security personnel at the Class IIB Detention Center in Padang and disciplinary sanctions must be enforced for inmates (inmates) who commit violence against other inmates as stated in the Ministry of Law and Human Rights Law Number 6 of 2013.